Effect of glucose concentration and cultivation days on Chlorella vulgaris growth via immobilization technique for biodiesel production - Noor Raihana, Abu Sepian; Nur Hidayah, Mat Yasin; N., Zainol (IOP Publishing, 2020)
Immobilization technique had been utilized to simplify the separation process of microalgae biomass for biodiesel production in the present study. The optimization using response surface methodology (RSM) through central composite design (CCD) approach had been applied to maximize the number of cells growth and minimized the cells loss of Chlorella vulgaris cells via immobilization technique. Two effects were optimized by CCD consisting of glucose concentration and cultivation days. The glucose concentration at 23.99 g/L and 7.96 days of cultivation time were found to be the optimum conditions for the maximum number of cells growth (3.30 × 109 cells/mL) and a minimum number of cells lost (1.07 × 104 cells/mL). The optimization using CCD had increased the lipid to 51.6 % and the result of fatty acid methyl ester (FAME) profile is similar to non-bearing oil crop. The findings had revealed the potential of immobilized microalgae biomass as an alternative feedstock for biodiesel production. Moreover, this study had reported optimum conditions for an efficient recovery process via immobilization technique using mixed matrices.